Cerebrospinal fluid proteomic profiling reveals potential biomarkers and altered pathways in myotonic dystrophy type 1 - Zafarullah, Marwa; Kamali, Tahereh; Hagerman, Katharine A.; Ghiglieri, Lisa; Duong, Tina; Wang, Eric; Sampson, Jacinda B.; Day, John W. (Frontiers in Neuroscience, 2025)
IntroductionMyotonic dystrophy (DM), the most common adult-onset muscular dystrophy, affects not only motor function and muscle integrity but also leads to debilitating cardiopulmonary, gastrointestinal, and multisystem complications. Central nervous system (CNS) involvement is increasingly recognized, manifesting as impairments in working memory, executive function, sleep regulation, and mood and behavior. These interrelated, multisystemic features contribute to multifaceted symptoms that significantly reduce quality of life for patients and their families. To identify potential biomarkers of CNS disease activity in DM1, we performed the first exploratory cerebrospinal fluid (CSF) proteomic profiling study.MethodsCSF samples from patients with DM1 (n = 11) and healthy controls (n = 5) were analyzed using Olink monoclonal antibody panels, quantifying 1,072 proteins. LASSO (Least Absolute Shrinkage and Selection Operator) regression identified proteins discriminating between DM1 and controls. Pathway enrichment analysis was performed using the Reactome database to assess biological significance.ResultsSix candidate biomarker proteins were differentially expressed between between DM1 patients and controls: CKAP4, SCARF1, NCAM1, CD59, PTH1R, and CA4. LASSO analysis further identified 15 proteins discriminating DM1 and controls, implicating pathways related to neuronal health, neuroinflammation, cognitive impairment, skeletal abnormalities, motor control, neuromuscular junction integrity, and cytoskeletal regulation. Dysregulated pathways included IGF transport, MAPK signaling, NCAM signaling, and broader signal transduction cascades pathways also implicated in other neurodevelopmental, neurodegenerative, and neuromuscular disorders.DiscussionThis first exploratory CSF proteomic analysis in DM1 identified dysregulated protein networks that may underlie CNS dysfunction in this multisystemic disease. These findings provide novel insights into DM1 pathophysiology and support the potential of CSF proteomic signatures as candidate diagnostic tools, indicators of disease activity, and measures of therapeutic response, pending validation in larger, independent cohorts.